2019
DOI: 10.5588/pha.19.0046
|View full text |Cite
|
Sign up to set email alerts
|

The burden of non-TB lung disease presenting to TB clinics in The Gambia: preliminary data in the Xpert® MTB/Rif era

Abstract: In some low and middle-income countries, 10–20% of patients presenting with a persistent cough have tuberculosis (TB). Once TB is excluded, health service provision for alternative diagnoses is limited. We prospectively studied patients with two Xpert-negative sputum results presenting to a TB clinic in The Gambia. Of 239 patients, 108 did not have TB; 65/102 (6 were lost to follow-up) had alternative diagnoses, 24.6% of which were non-respiratory; 37/102 had no diagnosis, 27.0% of whom were HIV-1-positive; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 8 publications
0
20
2
Order By: Relevance
“…An outpatient research clinic pilot study in The Gambia reports a similar finding of cardiac abnormalities being prevalent among patients without TB (n=108). 21 The prevalence of cardiac abnormalities in our study is higher than in The Gambia (26.3% vs 20%). 21 Cardiac abnormality diagnosis in The Gambia was through clinical assessment, ECG and echocardiography (as indicated) versus CXR only in our study.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…An outpatient research clinic pilot study in The Gambia reports a similar finding of cardiac abnormalities being prevalent among patients without TB (n=108). 21 The prevalence of cardiac abnormalities in our study is higher than in The Gambia (26.3% vs 20%). 21 Cardiac abnormality diagnosis in The Gambia was through clinical assessment, ECG and echocardiography (as indicated) versus CXR only in our study.…”
Section: Discussioncontrasting
confidence: 65%
“…21 The prevalence of cardiac abnormalities in our study is higher than in The Gambia (26.3% vs 20%). 21 Cardiac abnormality diagnosis in The Gambia was through clinical assessment, ECG and echocardiography (as indicated) versus CXR only in our study. This, together with higher median age in our study compared with The Gambia (51 years vs 40 years), could explain our higher observed prevalence.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…There were seven studies including (Table 1a) 6,17,[19][20][21][22][23] and five studies not including (Table 1b) 18,[24][25][26][27] clinically diagnosed tuberculosis cases that used passive case finding strategies. Of the five studies (Table 1b) not including clinically diagnosed tuberculosis cases, only Dorman et al (2018) 25 did not document whether a clinical assessment was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Only five studies reported diagnoses other than active tuberculosis (Table 4). 6,20,21,26,33 Two described non-tuberculous mycobacteria and one Pneumocystis jirovecii pneumonia as the only alternative diagnoses. 20,26,33 reported giving empirical antibiotics to all patients subsequently found not to have active tuberculosis amounting to mass administration of antibiotics to 207 and 380 patients respectively.…”
Section: Resultsmentioning
confidence: 99%